Peningkatan Kemampuan Berkomunikasi dengan Menerapkan Metode Bercakap-Cakap pada Siswa Kelompok A TK Aisyiyah 1 Sawahan - Hery Setiyatna (Fakultas Ilmu Tarbiyah dan Keguruan (FITK), Institut Agama Islam Negeri (IAIN) Surakarta, 2017)
The research aims to report the improvement of the kindergarten students’ communication skill by implementing the chatting technique. This study is a collaborative action research. The subjects are group A kindergarten students at TK Aisyiyah 1 Sawahan. The data is collected by field notes then analyzed with comparative analysis and interactive techniques. Performance indicators for this research are the average child reaches the ability to communicate for (1) 50% in the first cycle, (2) 60% in the second cycle, and (3) 75% in the third cycle. This study was conducted in three cycles and each cycle consists of: (1) Planning, (2) Acting, (3) Observing and (4) Reflecting.The result of this research indicated that chatting technique can improve the communication skill of group A kindergarten students in TK Aisyiyah 1 Sawahan, as teachers doing some reflections, the process of learning activities focused on students, and students were actively involved in the activities. The percentage of students communication skill before the action was less than 25%, the percentage of students' ability to communicate after the action on the first cycle increased to 43.75%, in the second cycle increased to 75%, in the third cycle increased to 93.75%.Keywords: chatting technique, communication skill, Group A kindergarten students